A short lecture on subjectivity - Wielecki, Krzysztof (Journal of Public Governance, 2014)
The concept of subjectivity can help in the reflection on the ontological status of the human being and his or her community, and on the relations between people and communities, as well as the importance of a human being within the communities. This concept can and should be the outset of a reflection on society, the state, politics, humanity, mental health, and identity. This paper drafts a theory of subjectivity at a time of the contemporary civilizational crisis, when humans and values often get lost in the liquid reality.